Distribution of Different Fractions of Boron in Soils of Konkan Region of India - KASTURE, M C; MORE, S S; KAPSE, V D; JADHAV, S C (Journal of the Indian Society of Coastal Agricultural Research, 2020)
The present study was conducted to assess the status of boron fractions in different soils of Konkan region. Surface soil samples were collected representing eight soil types, namely, lateritic, medium black, deep black, coarse shallow, coastal alluvial, coastal saline, reddish brown and acid sulphate soils located in different parts of Konkan region of Maharashtra. In general, the soils of the Konkan region of Maharashtra are acidic to neutral in reaction (pH 4.50 to 7.39) with low electrical conductivity values. The soils are fairly supplied with organic carbon (9.10 to 24.4 g kg-1). The available nitrogen and phosphorus content is low to medium in all types of the soils. The available potassium content is variable and ranges from low to high. The mean values of readily soluble boron (RsB), specifically adsorbed boron (SaB), oxide bound boron (OxB), organically bound boron (OrB), residual boron (ReB) and total boron (TB) were 0.32, 2.30, 58.90, 5.49, 85.72 and 152.73 mg kg-1, respectively. Most of the soils in Konkan region showed low to medium concentrations of readily soluble boron which is the plant available fraction of boron. The readily soluble boron ranged between 0.28 ppm to 0.34 ppm in different soils of the Konkan region of Maharashtra.